Enhancing the mechanical properties and surface morphology of individualized Ti-mesh fabricated through additive manufacturing for the treatment of alveolar bone defects - Wang, Lingxu; Wang, Fangfang; Ayisen, Saimi; Ren, Tianshui; Luo, Xiaoping; Wang, Penglai (Frontiers in Bioengineering and Biotechnology, 2023)
Titanium meshes are widely utilized in alveolar bone augmentation, and this study aims to enhance the properties of titanium meshes through heat treatment (HT) and the synergistic finishing technology of electric field and flow field (EFSF). Our findings illustrate that the titanium mesh exhibits improved mechanical properties following HT treatment. The innovative EFSF technique, in combination with HT, has a substantial impact on improving the surface properties of titanium meshes. HT initiates grain fusion and reduces surface pores, resulting in enhanced tensile and elongation properties. EFSF further enhances these improvements by significantly reducing surface roughness and eliminating adhered titanium powder, a byproduct of selective laser melting printing. Increased hydrophilicity and surface-free energy are achieved after EFSF treatment. Notably, the EFSF-treated titanium mesh exhibits reduced bacterial adhesion and is non-toxic to osteoblast proliferation. These advancements increase its suitability for clinical alveolar bone augmentation.